Instrumen Green Sukuk Dalam Mendukung Pembangunan Infrastruktur - Insanush Shofa; Khilfatul Khamidah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
Green sukuk is a new financial instrument designed to help Indonesia fulfill its commitment to growth in accounting flows in the economy but is also important for sustainable development that is in line with environmental welfare efforts. State development funding is the main thing in infrastructure development in various countries. The government will finance several road and bridge infrastructure developments using state sharia securities (SBSN) aka sukuk. The development of sukuk in Indonesia has always increased from 2013 to November 2018. Basically, the majority of Indonesians are Muslims and what is the strategy for developing sukuk as a sharia capital market product so that it plays a significant role in infrastructure development in Indonesia. Analysis is used to provide a clear picture starting from the benefits of sukuk and the role of sukuk in development. The results of the study show that the planning process for issuing Green Sukuk aims to align programs to ensure synergy/convergence of all government and community activities in optimizing sukuk development. Issuance of "Green Sukuk" as an Effort to Increase the Sukuk Market Share. As a new product, Green Sukuk still faces several obstacles. Among other things, clear and specific regulations governing Green Sukuk are needed. As well as creating a sharia basis regarding the issuance of Green Sukuk. The second strategy is to form an APS (Accelerated Sukuk Development) Team. This team is a forum or organization that was formed to accommodate the acceleration and growth of sharia bonds or sukuk.